(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay, which reproposes the issue of female detention, in the awareness that it must be understood and addressed from a cultural perspective that recognizes the presence of a gender difference and therefore of a specificity of female detention compared to male detention, analyzes subsequent developments regulatory and jurisprudential issues, finally questioning the scope of the most recent proposals for regulatory reform as well as the interventions envisaged in this regard by the PNRR, in order to examine their adherence to the relevant constitutional principles.